1977
DOI: 10.1136/gut.18.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine synthetase activity of the colonic mucosa in ulcerative colitis and Crohn's disease.

Abstract: SUMMARY Glucosamine synthetase is the first enzyme in glycoprotein biosynthesis, catalysing the formation of glucosamine-6-phosphate, from which N-acetylglucosamine is formed. The levels of this enzyme in normal human colonic mucosa (in colectomy specimens and rectal biopsies) were found to be 13-8 4 0 pmol glucosamine synthesised/h/g wet wt. In the colonic mucosa in ulcerative colitis and Crohn's colitis the enzyme level was diminished when there was loss of epithelial cells in the mucosa, although not when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 19 publications
2
13
1
Order By: Relevance
“…However, the thickness of the adherent mucus gel was found generally lower or unchanged [44,49], possibly due to excessive removal. In severe UC, both synthesis of mucins and the thickness of mucus barrier substantially declined [48][49][50]. The decreased mucin levels confirmed that the lower lipid/protein ratio in UC is due to an even larger scale of reduction in lipids.…”
Section: Discussionsupporting
confidence: 52%
“…However, the thickness of the adherent mucus gel was found generally lower or unchanged [44,49], possibly due to excessive removal. In severe UC, both synthesis of mucins and the thickness of mucus barrier substantially declined [48][49][50]. The decreased mucin levels confirmed that the lower lipid/protein ratio in UC is due to an even larger scale of reduction in lipids.…”
Section: Discussionsupporting
confidence: 52%
“…An other argument was that increased lysozyme-mediated glycocalyx production compensates for the thinning cell coat. In this context other characteristics of Crohn's dis ease, which are partially contradictory, are worth mention ing: (1) increased glycosamine synthetase activity in the bowel wall as a possible histochemical correlative to the compensalorily enhanced mucous glycocalyx production [Goodman et al, 1976[Goodman et al, , 1977 as well as decreased glyco protein synthesis in histologically unaffected bowel areas, resulting in impaired protection of the bowel mucosa [Bur ton and Anderson, 1983], and (2) reduced brush border enzyme activity as a possible equivalent to the shortened and damaged microvilli [Dunne et al, 1977;Doumiashkin et al, 1981], resulting in a decreased capacity to digest ingested macromolecules. …”
Section: Paneth Cellsmentioning
confidence: 99%
“…It may represent an inherent abnormality in gastrointestinal mucosa or a protective response to a faecal factor. 58 The lack of change in rectal glucosamine synthetase activity in the control group after faecal diversion suggests that the presence of faeces in the normal colon has little influence on glycoprotein synthesis and is in keeping with the reported lack of change in other mucosal enzymes after proximal diversion or small bowel resection. "…”
Section: Discussionmentioning
confidence: 67%